Safety and Effectiveness of Long-Term Exercise Interventions in Older Adults: A Systematic Review and Meta-analysis of Randomized Controlled Trials - García-Hermoso, Antonio; Ramirez-Vélez, Robinson; Sáez de Asteasu, Mikel L.; Martínez-Velilla, Nicolás; Zambom-Ferraresi, Fabricio; Valenzuela, Pedro L.; Lucia, Alejandro; Izquierdo, Mikel (Sports medicine (Auckland), 2020)
Background Physical exercise is beneficial to reduce the risk of several conditions associated with advanced age, but to our knowledge, no previous study has examined the association of long-term exercise interventions (≥ 1 year) with the occurrence of dropouts due to health issues and mortality, or the effectiveness of physical exercise versus usual primary care interventions on health-related outcomes in older adults (≥ 65 years old). Objective To analyze the safety and effectiveness of long-term exercise interventions in older adults. Methods We conducted a systematic review with meta-analysis examining the association of long-term exercise interventions (≥ 1 year) with dropouts from the corresponding study due to health issues and mortality (primary endpoint), and the effects of these interventions on health-related outcomes (falls and fall-associated injuries, fractures, physical function, quality of life, and cognition) (secondary endpoints). Results Ninety-three RCTs and six secondary studies met the inclusion criteria and were included in the analyses ( n = 28,523 participants, mean age 74.2 years). No differences were found between the exercise and control groups for the risk of dropouts due to health issues (RR = 1.05, 95% CI 0.95–1.17) or mortality (RR = 0.93, 95% CI 0.83–1.04), although a lower mortality risk was observed in the former group when separately analyzing clinical populations (RR = 0.67, 95% CI 0.48–0.95). Exercise significantly reduced the number of falls and fall-associated injuries, and improved physical function and cognition. These results seemed independent of participants’ baseline characteristics (age, physical function, and cognitive status) and exercise frequency. Conclusions Long-term exercise training does not overall influence the risk of dropouts due to health issues or mortality in older adults, and results in a reduced mortality risk in clinical populations. Moreover, exercise reduces the number of falls and fall-associated injuries, and improves physical function and cognition in this population.